2022
DOI: 10.3390/vaccines10101715
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Willingness to Receive a COVID-19 Vaccine in Adult Polish Population—A Cross-Sectional Survey

Abstract: Vaccinations are proven to be the most efficient in preventing COVID-19 disease. Nonetheless, some people are skeptical and hesitant. The study aimed to determine factors associated with willingness to receive a COVID-19 vaccine in the Polish adult population. An online survey consisting of questions regarding (1) demographic information and (2) health issues (the status of vaccination, comorbidities, receiving the flu vaccine and usage of health monitoring apps) was distributed between 13 January and 14 Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…This contrasts with other studies that reported higher vaccine willingness with HCWs with underlying diseases or conditions 53,54 . It may be because the influence of co‐morbidities and prior COVID‐19 diagnosis on vaccine willingness could vary by region, depending on factors such as local healthcare infrastructure and public health messaging 55,56 …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This contrasts with other studies that reported higher vaccine willingness with HCWs with underlying diseases or conditions 53,54 . It may be because the influence of co‐morbidities and prior COVID‐19 diagnosis on vaccine willingness could vary by region, depending on factors such as local healthcare infrastructure and public health messaging 55,56 …”
Section: Discussionmentioning
confidence: 76%
“…53,54 It may be because the influence of co-morbidities and prior COVID-19 diagnosis on vaccine willingness could vary by region, depending on factors such as local healthcare infrastructure and public health messaging. 55,56 HCWs with less than a high school education had a higher vaccination coverage rate, indicating that a larger proportion of them had received at least one dose of the COVID-19 vaccine. It may be because people with low educational attainment know less about vaccines and worry less about safety.…”
Section: Contextual Influencementioning
confidence: 99%
“…The aim of our study is twofold: to understand how contracting COVID-19 affects sleep and mental health and to evaluate how a previous mild COVID-19 infection impacts results on endurance performance scores among EAs. These are aspects that we will struggle with during the pandemic, and EA will have to find solutions to counteract them until a fully effective vaccine or drug is found and the population shows a greater willingness to use vaccinations [25].…”
Section: Introductionmentioning
confidence: 99%
“…New, pandemic conditions became a challenge for sportsmen. Although, athletes are not considered a high-risk group for high COVID-19 vaccine hesitancy (Ulaszewska et al, 2022). Moreover, about 94% of them, the course of the illness is asymptomatic or mild (Lemes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%